Asociated factors to pulmonar tuberculosis incidence in a marginal urban health center of Lima 1999-2008 - Crispín, Víctor (2010)
Tuberculosis is a public health problem, generated by poverty, with high prevalence and incidence. The objetives of this study were to determine the associated factors to tuberculosis in a marginal urban health center of Lima. This is an observational study of case report undertaken in Chaclacayo since January 1999 to December 2008. The data collected was acquired from the routine reports of the National Control Program. A total of 197 cases were evaluated; 108 were men (55%) and 89 were women (45%). Within these 197 subjects, 151 were new cases (76.6%) and 32 were individuals who had been previously diagnosed with tuberculosis (16.2%). The incidence decreased from 305 x 100 000 in 1999 to 119 x 100 000 inhabitants in 2008. The more affected age groups were 15-29 years with 103 cases (52.3%). 174 patients showed a high prevalence of pulmonary tuberculosis (88%); successful treatment were completed in 176 cases (89,3%), 14 were defaulted (7%). 20 cases had personal antecedents (10%) and 106 had familial antecedents (54%). In 152 cases, the family had more than 5 members (77%). 47 were mistress of the house (24%); 44 were students (22%), 24 were laborers (12%) and 42 were unemployed individuals or without answer (21%). In conclusion, there were a high incidence of tuberculosis, the pulmonary form with smear positive was predominant, affecting young people, 90% of cases were cured, the personal o familial antecedent of tuberculosis was a frequent factor.